Mutlaq dan Muqayyad Sebagai Instrumen Pembacaan Teks Hukum Islam: Kajian Ushuliyah - Taqwim, Andi Ahsan; H, Darmawati; Amin, Abdul Rauf Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of lafadz with absolute and or limited capacity (muqayyad) is one of the beauties of Arabic rhetoric. And in that indisputable Book, he was acquainted with the absoluteness of the Quran wa muqayyaduh or the absoluteness of the Qur’an and its limitations. In this article will discuss the meaning of absolute and muqayyad, examples of absolute and muqayyad lafadz, the law of absolute and muqayyad lafadz, and the division of absolute and muqayyad lafadz. The purpose of this discussion is for the reader to understand the concepts of absolute and muqayyad more deeply. By understanding the meaning of a particular verse, a believer will more easily obtain a legal ruling. Law has been established , then it will be easier for anyone to apply it. Absolute and muqayyad are fundamental concepts in jurisprudence that serve as guidelines in understanding and extracting law from the nash-nash of Shariah. Absolute is a pronoun that expresses a general meaning without any particular restriction, whereas a muqayyad is a pronoun that is limited by a specific attribute, condition, or condition. Both play an important role in a careful and responsible legal istinbath process.